2018
DOI: 10.1038/s41598-018-33590-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between circulating tumor necrosis factor-related biomarkers and estimated glomerular filtration rate in type 2 diabetes

Abstract: Chronic inflammation plays a crucial role in the development/progression of diabetic kidney disease. The involvement of tumor necrosis factor (TNF)-related biomarkers [TNFα, progranulin (PGRN), TNF receptors (TNFR1 and TNFR2)] and uric acid (UA) in renal function decline was investigated in patients with type 2 diabetes (T2D). Serum TNF-related biomarkers and UA levels were measured in 594 Japanese patients with T2D and an eGFR ≥30 mL/min/1.73 m2. Four TNF-related biomarkers and UA were negatively associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 41 publications
2
25
1
Order By: Relevance
“…The molecular weight of sTNFR1 is just 55 KD, and despite some presumed ectodomain cleavage of the receptor, is the predominant form of sTNFR1 found in human sera 12 . A contribution of plasma accumulation of the receptor as GFR declines through reduced renal clearance is therefore possible and, indeed, sTNFR1 levels are detectable in urine, and serum levels have been reported to correlate with eGFR in cross-sectional studies [13][14][15] . However, the present results could also be consistent with the growing body of evidence implicating sTNFR in the pathogenic processes that promote GFR loss in diabetes 6,16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…The molecular weight of sTNFR1 is just 55 KD, and despite some presumed ectodomain cleavage of the receptor, is the predominant form of sTNFR1 found in human sera 12 . A contribution of plasma accumulation of the receptor as GFR declines through reduced renal clearance is therefore possible and, indeed, sTNFR1 levels are detectable in urine, and serum levels have been reported to correlate with eGFR in cross-sectional studies [13][14][15] . However, the present results could also be consistent with the growing body of evidence implicating sTNFR in the pathogenic processes that promote GFR loss in diabetes 6,16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of serum biomarkers is an interesting approach to assess (patho)physiological processes and therapeutic responses. Serum biomarkers are used in the identification and management of several diseases, including heart failure [5], myocardial infarction [6], cancer [7], and diabetes [8]. So far, no specific serum biomarkers to assess AF stage and to predict the outcome of AF treatment are available.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported increased circulating PGRN concentrations in patients with metabolic diseases such as diabetes and obesity 6 , 7 . Additionally, we have previously shown that circulating PGRN concentrations are significantly increased in patients with type 2 diabetes and renal functional decline 8 . These findings raise the possibility that PGRN may exert beneficial or harmful effects depending on the affected organ or pathological condition.…”
Section: Introductionmentioning
confidence: 93%